Functionalized nanoceria exhibit improved angiogenic properties - Nethi, Susheel Kumar (2020)
The growth of new blood vessels from the pre-existing vasculature known as angiogenesis has a vital role in various physiological and pathological processes. In the present study, we demonstrate the pro-angiogenic properties of functional nanoconjugates of organosilane functionalized cerium oxide (CeO2) nanoparticles (nanoceria). Aqueous dispersible CeO2 and trivalent metal (samarium) ion-doped CeO2 (SmCeO2) nanoparticles conjugated with hydrophilic biocompatible and antifouling (6-{2-[2-(2-methoxy-ethoxy)-ethoxy]-ethoxy}-hexyl)triethoxysilane moieties were prepared. These functional nanoconjugates were prepared via an in situ synthesis and functionalization procedure using an ammonia-induced ethylene glycol-assisted precipitation method. The prepared nanoconjugates were thoroughly characterized using various physico-chemical techniques such as transmission electron microscopy (TEM), X-ray diffraction (XRD) analysis, dynamic light scattering (DLS), Fourier-transform infrared (FTIR) spectroscopy, 13C high-resolution solid-state nuclear magnetic resonance (NMR) spectroscopy, and X-ray photoelectron spectroscopy (XPS). The pro-angiogenic properties of the prepared nanoconjugates were evaluated by employing various angiogenesis assays (in vitro and in vivo). The results of the present study illustrate that the functional nanoconjugates of SmCeO2 triggered endothelial cell proliferation and induced the growth of blood vessels in a chick embryo. The enhanced expression of pro-angiogenic markers (p38 MAPK/HIF-1α) by these functional nanoconjugates might be a plausible signaling mechanism underlying their pro-angiogenic properties. Considering all the observations, we believe that (6-{2-[2-(2-methoxy-ethoxy)-ethoxy]-ethoxy}-hexyl)triethoxysilane conjugated SmCeO2 nanoparticles could be developed as potential candidates for the treatment of cardiovascular, ischemic and ocular diseases where angiogenesis is the principal phenomenon.